1999
DOI: 10.1128/jvi.73.4.3338-3350.1999
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Persistent Infection of Human Neural Cell Lines by Human Coronavirus OC43

Abstract: Human coronaviruses (HuCV) are recognized respiratory pathogens. Data accumulated by different laboratories suggest their neurotropic potential. For example, primary cultures of human astrocytes and microglia were shown to be susceptible to an infection by the OC43 strain of HuCV (A. Bonavia, N. Arbour, V. W. Yong, and P. J. Talbot, J. Virol. 71:800–806, 1997). We speculate that the neurotropism of HuCV will lead to persistence within the central nervous system, as was observed for murine coronaviruses. As a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
1
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(144 citation statements)
references
References 82 publications
2
138
1
3
Order By: Relevance
“…neuroinvasive in humans and suggests that they establish a persistent infection in human CNS (Arbour et al, 2000). Furthermore, we have shown that these viruses are able to establish a persistent infection in human cells representative of the CNS (Arbour et al, 1999a(Arbour et al, , 1999b and that HCoV-OC43 RNA could be detected for at least a year in the CNS of infected mice that survived the acute encephalitis. A significant portion of these surviving mice exhibited abnormal reflexes shown by limb clasping, presented clinical signs of decreased activity in an open field test, and had a smaller hippocampus associated with a loss of hippocampal neurons, particularly in the CA1 and CA3 layers (Jacomy et al, 2006), similar to what is seen after neuroinvasion of the CNS by the influenza A virus (Jurgens et al, 2012).…”
Section: Human Coronaviruses In the Cnsmentioning
confidence: 80%
See 1 more Smart Citation
“…neuroinvasive in humans and suggests that they establish a persistent infection in human CNS (Arbour et al, 2000). Furthermore, we have shown that these viruses are able to establish a persistent infection in human cells representative of the CNS (Arbour et al, 1999a(Arbour et al, , 1999b and that HCoV-OC43 RNA could be detected for at least a year in the CNS of infected mice that survived the acute encephalitis. A significant portion of these surviving mice exhibited abnormal reflexes shown by limb clasping, presented clinical signs of decreased activity in an open field test, and had a smaller hippocampus associated with a loss of hippocampal neurons, particularly in the CA1 and CA3 layers (Jacomy et al, 2006), similar to what is seen after neuroinvasion of the CNS by the influenza A virus (Jurgens et al, 2012).…”
Section: Human Coronaviruses In the Cnsmentioning
confidence: 80%
“…Up until now, no clear specific association has ever been made with any known human neuropathology. However, even though the mechanism by which they reach the human CNS is still to be decrypted, at least three of the six coronaviruses that infect humans were shown to be neuroinvasive and neurotropic in humans: HCoV-229E and HCoV-OC43 (Arbour et al, 1999a(Arbour et al, , 1999b(Arbour et al, , 2000Bonavia et al, 1997), as well as SARS-CoV (Gu et al, 2005;Xu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…15 On skin, infectivity of parainfluenza virus decreased rapidly but remained detectable for up to 1 h. 15,18 On the other hand, RSV could be recovered from a skin surface for not more than 20 min 8 and rhinoviruses could survive for 1-3 h. 9 We have not tested survival of HCoV on human skin because of ethical concerns regarding the risk of acute respiratory tract infection and possible neurological damage. 19,20 To prevent or reduce the possibility of personto-person transmission of viruses via surfaces, their disinfection is important. Therefore, we tested the disinfecting activity against HCoV of four classes of disinfectants that are widely used in hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent descriptions of novel BetaCoV1 members or relatives in rodents suggest them as primordial hosts (Hu et al, 2017;Lau et al, 2015;Wang et al, 2015). HCoV-OC43 was found to have tropism for neural cells in vitro and in experimentally infected mice, resembling MHV (Arbour et al, 1999;Jacomy et al, 2006). Presence of virus in the central nervous system was reported in patients with chronic demyelinating disease and acute encephalomyelitis (Morfopoulou et al, 2016;Murray et al, 1992;Yeh et al, 2004).…”
Section: Hcov-oc43mentioning
confidence: 98%